Occurrences of 2-methylisoborneol and geosmin –degrading bacteria in a eutrophic reservoir and the role of cell-bound versus dissolved fractions. (1st November 2021) - Clercin, Nicolas A.; Druschel, Gregory K.; Gray, Mark
Abstract: As taste-and-odor outbreaks are common in surface waters worldwide, extensive studies have focused on the identification of microorganisms involved in the production of 2-methylisoborneol (MIB) and geosmin (GSM). However, fewer studies have tried to identify potential degraders in natural environments. Eagle Creek Reservoir, a temperate and eutrophic water body, experienced two major seasonal odorous outbreaks in 2013 with maximal concentrations of 99.1 (MIB) and 77.3 ng L −1 (GSM). Fractionation analyses of the odorous compounds showed that MIB was found more frequently in the dissolved fraction while GSM was mostly cell-bound. This difference likely impacts taste-and-odor (T&O) compound susceptibility to biodegradation by bacteria. Spearman relationships of epilimnetic samples collected between spring and early fall linked dissolved MIB occurrences to higher abundances of Bacteroidetes like Flavobacterium resistens, F. granuli, F. saliperosum ( p < 0.001), F. kamogawaensis ( p < 0.01) capable of MIB degradation. Occurrences of cell-bound GSM were correlated to two α-Proteobacteria Novosphingobium hassiacum ( p < 0.001) and Sphingomonas oligophenolica ( p < 0.01), both identified as potential degraders of GSM. The roles of Pseudomonas and Bacillus were ambiguous, and these genera might have been involved in both compound biodegradations ( p < 0.05). Graphical abstract: Image 1 Highlights: Seasonal odorous events in reservoir generate MIB and geosmin compounds. α-Proteobacteria and Bacteriodetes are the dominant MIB and geosmin degraders. Geosmin is prevalently cell-bound whereas MIB is dissolved. Novosphingobium and Sphingomonas are involved in geosmin biodegradation; Flavobacterium degrade MIB.